GLOBALISAI MELAYU: PELUANG DAN TANTANGAN MEMBANGUN IDENTITAS MELAYU DALAM KONTEKS MODERNITAS - Ihsan Sanusi (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2017)
This essay discusses the diaspora of the Malay world. It actually resembles a nation or group of ethnics cognate that share the same religion and use the same language. In the context of modernity, it is time for Malays to collectively improve their view of Malay by building a different paradigm in the horizontal level through the not-cramped perspective of lokaism, because it is something that is not singular (heterogeneous). So, Malays can identify themselves and make a significant contribution to the global civilization scene. Within the framework of identification and revitalization of Malay, it requires support from various components, both intellectuals and experts, as well as the holders and policy makers in several Malay State nations. A further consequence is the emergence of a kind of strategic alliance between Malays in order to develop science and technology, politics, economics, culture, education and others. Thus, in the context of the modernity of Malay civilization that has found its identity will be advanced as well as will be able to influence the great civilization of the world.